FAKTOR RISIKO PENINGKATAN TEKANAN DARAH PADA KELOMPOK USIA 17-35 TAHUN DI DESA WALEO DUA - Glenda Freeisi Makalew; Mario Esau Katuuk; Hendro Joli Bidjuni (Universitas Sam Ratulangi, 2023)
Background: The increase of blood pressure is caused by several factors, namely genetics, age, gender, obesity, race and lifestyle habits such as high salt consumption, overeating, stress, physical activity, smoking, alcohol consumption and taking drugs. Purpose : It is known the factors that associated with increase of blood pressure in the 17-35 year age group in Waleo Dua village. Method: The quantitative approach is correlational with the type of analytic observational research with a cross sectional design. Sample: sampling using the purposive sampling method and to determine the sample size using the Slovin formula, with a total sample of 122 respondents. Result: This study used the Chi-Square statistical test and Spearman Rank test, and showed a significant relationship between gender (p=0.005), body mass index (p=0.000, r=0.368), physical activity (p=0.001, r=-0.285), sodium-eating pattern (p=0.000, r=0.413), fat-eating pattern (p=0.000, r=0.432) and alcohol consumption (p=0.006, r=0.247) and there was no significant relationship from family history (p=0.914) and stress (p=0.132, r=0.137) with an increased in blood pressure. Conclusion: there are correlations between gender, body mass index, physical activity, dietery pattern (sodium and fat) and alcohol consumption with an increase of blood pressure. Suggestion: Checking blood pressure and implementing a healthy lifestyle can prevent an increase of blood pressure. Keywords: Risk Factor; The Increase of Blood Pressure; Late Adolescence; Young Adult